Studies in English Organ Music - Quinn, Iain 1973- (Ashgate historical keyboard series, 2018)
Studies in English Organ Music is a collection of essays by expert authors that examines key areas of the repertoire in the history of organ music in England. The essays on repertoire are placed alongside supporting studies in organ building and liturgical practice in order to provide a comprehensive contextualization. An analysis of the symbiotic relationship between the organ, liturgy, and composers reveals how the repertoire has been shaped by these complementary areas and developed through history. This volume is the first collection of specialist studies related to the field of English organ music